A Giant Antenatal Hydronephrosis as a Reason of Late Pregnancy Termination a Fetal Autopsy Case - Hasanov, Adalat; Musayev, Jamal; Karimova, Ilaha; Zeynalov, Hikmat (The Bulletin of Legal Medicine, 2015)
The late termination of pregnancy constitutes the important medical and ethic problems around the world. There should be serious medical and social indications for termination of pregnancy in this period. Here, a case of late termination of pregnancy with the request of the parents due to antenatal hydronephrosis was presented. Antenatal hydronephrosis does not constitute a serious indication for late pregnancy termination because of its spontaneous regression and the availability of treatment options postnatally. The termination of pregnancy due to such reasons is risky, especially in late period of pregnancy, which abortion complications are frequent. In this regard, giving sufficient information about presented disease, its course and treatment to future mother and her family by healthcare workers is important.Key words: Antenatal hydronephrosis, fetus, autopsy, ultrasonography.
Keywords: antenatal hydronephrosis; fetus; autopsy; ultrasonography